대학의 디자인 교과목에서 플립드러닝 적용사례 및 효과성 검증 연구 - 임유진; Lim Eugene; 김종선; Kim Jong Sun (기초조형학연구, 2019)
본 논문은 대학의 디자인 수업에서 플립드러닝 교수법의 효과성을 검증하고 효과적인 수업의 방법을 제시하는 것을 목적으로 한다. 플립드러닝 교수법을 적용한 교과목의 교육의 효과성을 검증하기 위해 플립드러닝이 적용된 디자인 교과목을 수강한 학생을 대상으로 사전-사후 검증을 실시하였다. 이를 위해 디자인씽킹과 디자인경영 교과목을 수강한 학습자들을 대상으로 본 연구에서 플립드러닝의 학습성과 요인으로 상정한 학업적 자기효능감, 자기조절학습능력, 교과흥미를 학기초와 학기말에 설문을 실시하여 플립드러닝의 효과성을 살펴보았다. 사전조사와 사후조사 설문에 모두 응답한 44명의 응답을 바탕으로 사전-사후 차이검증을 위해 t 검증 (matched pair t test)을 실시하였다. 또한 학기말에 플립드러닝 수업 전반에 대한 의견 및 개선점을 학습자들에게 물어 교수자가 플립드러닝 설계 및 운영 시 고려해야 할 사항을 도출하고자 하였다. 본 연구의 결과는 다음과 같다. 첫째, t 검정 분석결과, 본 연구에서 상정한 연구변인인 학습자의 학업적 자기효능감, 자기조절학습 능력, 교과흥미 모두 통계적으로 유의하게 향상된 것을 확인하였다. 이는 학습자가 학습의 주체가 되어 자기 스스로 학습과정을 점검 및 관리하고, 사전학습에서 습득한 지식을 수업 중에 다양한 활동을 통해 직접 적용해보며, 학습결과를 스스로 성찰해보는 기회가 증가함에 따라 나타나는 결과라고 해석될 수 있다. 둘째, 플립드러닝에 대한 학생들의 의견과 수업의 경험을 종합하여 플립드러닝 수업 설계 시 보완해야 할 점과 고려해야 할 점을 도출하였다. 학습자들의 의견 중 온라인 동영상에 대한 의견과 In-Class 토론 활동 시 운영에서 개선되어야 할 점들이 도출되어 이를 바탕으로 플립드러닝 운영전략을 Pre-Class(수업 전), In-Class(수업 중), Post-Class(수업 후)로 나누어 제시하였다. The purpose of this study is to verify the effectiveness of flipped learning (FL) and to suggest effective teaching methods in design courses at university settings. In order to determine the effectiveness of courses applying the FL teaching method, pre-post testing was conducted with students who were enrolled in design courses. The variables which were chosen as learning outcomes in the study- academic self-efficacy, self-regulated learning ability, and subject interest- were estimated at the beginning of the semester and at the end of the semester from students who took design thinking and design management courses. A matched pair t-test was conducted for the pre-post difference test based on the responses of 44 respondents who answered both the pre and post-test questionnaires. In addition, students were asked about feedback and improvement in the overall FL class at the end of the semester. We tried to draw out what to consider when designing and operating FL classes. The results of this study are as follows. First, from the result of the t-test, it was found that the learners' academic self-efficacy, self-regulated learning ability, and interest in the curriculum were statistically significantly increased. This result can be interpreted as an outcome of a series of self-regulated learning experiences, such as self-monitoring and managing of their learning process, that incorporated various activities that made students apply what they learned in the Pre-Class and increased self-reflection opportunities. Second, among students’ opinions, the feedback on online video and the operating strategy of In-Class discussion were found as key issues. Based on this study, FL teaching strategies from the design course were provided by dividing the research findings into Pre-Class, In-Class, Post-Class.